A cross-sectional study of the endorsement proportion of reporting guidelines in 1039 Chinese medical journals - Duan, Yuting; Zhao, Lingyun; Ma, Yanfang; Luo, Jingyuan; Chen, Juexuan; Miao, Jiangxia; Zhang, Xuan; Moher, David; Bian, Zhaoxiang (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Reporting quality is a critical issue in health sciences. Adopting the reporting guidelines has been approved to be an effective way of enhancing the reporting quality and transparency of clinical research. In 2012, we found that only 7 (7/1221, 0.6%) journals adopted the Consolidated Standards of Reporting Trials (CONSORT) statement in China. The aim of the study was to know the implementation status of CONSORT and other reporting guidelines about clinical studies in China. Methods A cross-sectional bibliometric study was conducted. Eight medical databases were systematically searched, and 1039 medical journals published in mainland China, Hong Kong, Macau, and Taiwan were included. The basic characteristics, including subject, language, publication place, journal-indexed databases, and journal impact factors were extracted. The endorsement of reporting guidelines was assessed by a modified 5-level evaluation tool, namely i) positive active, ii) positive weak, iii) passive moderate, iv) passive weak and v) none. Results Among included journals, 24.1% endorsed CONSORT, and 0.8% endorsed CONSORT extensions. For STROBE (STrengthening the Reporting of Observational Studies in Epidemiology), PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), STARD (An Updated List of Essential Items for Reporting Diagnostic Accuracy Studies), CARE (CAse REport guidelines), the endorsement proportion were 17.2, 16.6, 16.4, and 14.8% respectively. The endorsement proportion for SPIRIT (Standard Protocol Items: Recommendations for Interventional Trials), TRIPOD (Transparent Reporting of a Multivariable Prediction Model for Individual Prognosis or Diagnosis), AGREE (Appraisal of Guidelines, Research, and Evaluation), and RIGHT (Reporting Items for Practice Guidelines in Healthcare) were below 0.7%. Conclusions Our results showed that the implementation of reporting guidelines was low. We suggest the following initiatives including i) enhancing the level of journal endorsement for reporting guidelines; ii) strengthening the collaboration among authors, reviewers, editors, and other stakeholders; iii) providing training courses for stakeholders; iv) establishing bases for reporting guidelines network in China; v) adopting the endorsement of reporting guidelines in the policies of the China Periodicals Association (CPA); vi) promoting Chinese medical journals into the international evaluation system and publish in English.